Perforator Management with Endovenous Laser Ablation and its Role in the Treatment of Resistant Venous Ulcers - GAURAV KUMAR (International Journal of Anatomy Radiology and Surgery, 2021)
Introduction: Varicose vein disease can present in different patterns with pathological components being restricted to Great Saphenous Vein (GSV), Short Saphenous Vein (SSV), perforators or any combination of these. The role of perforators has been debated in the past especially for non-healing ulcers. Different methods of treatment have been used in the past for treatment of perforators with Endovenous Laser Ablation Therapy (EVLT) emerging as a promising modality. Aim: To calculate the rate of perforator closure post-EVLT and to study the patient’s progress using Revised Venous Clinical Severity Score (RVCSS) post-treatment of incompetent perforators in resistant cases of varicose vein. Materials and Methods: This prospective cohort longitudinal study comprised of 55 patients suffering from treatment resistant venous ulcer over a minimal period of three months with incompetent perforators even after the treatment of primary venous insufficiency. They were taken up for EVLT. The patients were followed-up for three months for healing of ulcer and improvement of symptoms using the RVCSS. Statistical analysis was done using Statistical Package For Social Science (SPSS version 24.0) and paired t-test was used to calculate the p-value at three weeks and three months. Results: Out of 55 patients, 45 consented for active perforator management. In that group of 45 patients, 75 incompetent perforators were identified and managed by EVLT. Rest 10 patients opted for the conservative management. The closure of perforator was found in 100% perforators with 95% of these patients showing healing of ulcers on follow-up. With treatment of incompetent perforators, there was a significant reduction in RVCSS from 9.44 to 4.16 when patients were followed-up after three months. Conclusion: The EVLT is an effective method in closure of the incompetent perforators in lower limb. The treatment of incompetent perforators is must, especially in cases of intractable/residual varicose vein disease.